Homogenisation of the electrothermal behaviour of granular material - Rooney, C (2019)
Granular material is a critical component of many industrial applications and is particularly important for metallurgical processes. In particular, granular carbon experiences electrical heating in a metallurgical furnace known as a calciner. As the temperature of the carbon increases, its chemical and physical properties transform, namely to resemble those of graphite. However, the high temperatures within the calciner make ex- perimental measurements very difficult to obtain. Consequently, a funda- mental understanding of the inner mechanisms of the process has proved to be most challenging.